Factors, mechanisms and improvement methods of muscle strength loss - Wang, Kaiyong; Wang, Xuyu; Wang, Yanqiu (Frontiers in Cell and Developmental Biology, 2024)
Muscle strength is a crucial aspect of muscle function, essential for maintaining normal physical activity and quality of life. The global aging population coupled with the increasing prevalence of muscle disorders and strength loss, poses a remarkable public health challenge. Understanding the mechanisms behind muscle strength decline is vital for improving public health outcomes. This review discusses recent research advancements on muscle strength loss from various perspectives, including factors contributing to muscle strength decline, the signaling pathways involved in the deterioration of muscle function, and the methods for assessing muscle strength. The final section explores the influence of exercise stimulation and nutrition on muscle strength.